Therapeutic relevance of targeted sequencing in management of patients with advanced biliary tract cancer: DNA damage repair gene mutations as a predictive biomarker. (October 2019) - Chae, Heejung; Kim, Deokhoon; Yoo, Changhoon; Kim, Kyu-pyo; Jeong, Jae Ho; Chang, Heung-Moon; Lee, Sang Soo; Park, Do Hyun; Song, Tae Jun; Hwang, Shin; Kim, Ki-Hun; Song, Gi-Won; et al.
Abstract: Purpose: In biliary tract cancer (BTC), standard chemotherapy has limited benefit and no molecular targeted agents have been approved. This study investigated the genetic profile of BTC to identify potential new therapeutic targets and predictive biomarkers. Methods: Targeted exome sequencing was performed for 124 patients with BTC [gallbladder cancer (GBC), 25; intrahepatic cholangiocarcinoma (ICC), 55; extrahepatic cholangiocarcinoma (ECC), 44]. Survival analysis was performed in 112 patients who received palliative chemotherapy for locally unresectable or metastatic disease. Results: Genetic alterations were observed in 104 patients (83.8%); the most commonly mutated genes were TP53 (44.4%), KRAS (29.0%), ARID1A (12.1%) and IDH1 (9.7%). IDH1/2 mutations appeared more frequently in ICC (23.6%, P = 0.0002) than in GBC (4.0%) or ECC (2.3%), while ERBB2 / 3 mutations were found only in GBC (20.0%) and ECC (11.4%). Patients harbouring TP53 mutations had shorter overall survival (OS; median 15.2 vs. 37.8 months, P  = 0.018), while IDH1 mutations showed a tendency for longer progression-free survival (PFS; 10.6 vs. 6.1 months, P  = 0.124). Potentially actionable genetic alterations were found in 54.8%, and 7.1% received appropriate molecular targeted therapy in the clinical trial setting. Germline or somatic mutations in DNA damage repair (DDR) genes were found in 63.5% of patients and were significantly associated with longer PFS (6.9 vs. 5.7 months, P  = 0.013) and OS (21.0 vs. 13.3 months, P  = 0.009) in patients who received first-line platinum-containing chemotherapies (n = 88). Conclusions: A subgroup of patients with BTC may benefit from targeted therapy by the aid of genetic information. In particular, DDR alterations may be a predictive biomarker for response to platinum-containing chemotherapy in patients with BTC. Highlights: We examined genetic landscape of biliary tract cancer with targeted sequencing. Certain genetic mutations were associated with clinical outcomes. More than half of patients harboured at least one potentially actionable alteration. DNA damage repair gene alterations were associated with a better response to platinum-based treatment.